Realitas Sejarah dan Dinamika Identitas Yahudi Nusantara - Epafras, Leonard Chrysostomos (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The history of Jewish Nusantara in Indonesia is unclear whether Jewish came to Indonesia or otherwise. The fact that in Indonesia regulation, Judaism is not part of religions officially recognized by the state, add more suspicions that Judaism is not well accepted in Indonesia. In addition, Indonesia people, objectively, factually and historically speaking, have no much information about Judaism either in terms of religion, social, cultural and politics. In terms of academic studies, Historical and scientific record are not yet capable to explore much information about them. On one hand, the history of Judaism in Indonesia (Yahudi Nusantara) is academically and culturally limited. On the other hand, public discussion and debate relating to this topic—which tend to describe Jews historically and stereotypically—are rising and growing. This article aims to narrow the gap between both of two mentioned realities to explore historical existence of Jews in Indonesia. It will elucidate specific moments when Jews reality has been transforming and challenging in the context of Indonesian culture. Using this paradigm, the article perceives Jews as a dynamic and moving survival, like other realities. Therefore, this article intends to build good understanding of Judaism, in general, and Indonesian Jews in particular.